The impact of capital ratio on lending of EU banks - the role of bank specialization and capitalization - Malgorzata Olszak; Mateusz Pipien; Sylwia Roszkowska (Institute of Economic Research (IER), 2015)
In this paper we aim to find out whether bank specialization and bank capitalization affect the relationship between bank loan growth and bank capital ratio, both in expansions and in contractions. We hypothesize that the impact of bank capital on lending is relatively strong in cooperative banks and savings banks. We also expect that this effect is nonlinear, and is stronger in 'low' capital banks than in 'high' capital banks. To test our hypotheses we apply two-step GMM robust estimator (Blundell & Bond, 1998) for data spanning the years 1996 - 2011 on individual banks available in the Bankscope database. Our analysis shows that lending of poorly capitalized banks is more affected by capital ratio than lending of well capitalized banks. Loan growth of cooperative and savings banks is more capital constrained that lending of commercial banks. Capital matters for the lending activity in contractions only in the case of savings and 'low' capital banks.
Keywords: E32; G21; G28; G32; 330; loan supply; capital ratio; procyclicality